2021
DOI: 10.52939/ijg.v17i2.1765
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rice Plant Height from a Low-Cost UAV- Based Lidar Point Clouds

Abstract: UAV systems are considered effective tools to collect information regarding crops. In this study, the rice growth was observed by a small UAV-based LiDAR system from above. For developing the system, DJI S800 was chosen as a platform on which a non- survey-grade laser scanner HOKUYO UTM30LX-EW was mounted. Field experiments were carried out from late June to late early August 2017 in Nagaoka city, Niigata Prefecture, Japan. Percentile analysis is applied to locate the top and bottom positions of rice plants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The UAVs discovered that the most significant factors were canopy cover, plant height, and Triangular Greenness Index (TGI), followed by Green Normalized Difference Vegetation (GNDVI) and Normalized Difference Vegetation Index (NDVI), respectively. To increase the accuracy of the plant height estimation, the Light Detection and Ranging (LIDAR) system was also applied [18]. The system is still an expensive technology to date.…”
Section: Discussionmentioning
confidence: 99%
“…The UAVs discovered that the most significant factors were canopy cover, plant height, and Triangular Greenness Index (TGI), followed by Green Normalized Difference Vegetation (GNDVI) and Normalized Difference Vegetation Index (NDVI), respectively. To increase the accuracy of the plant height estimation, the Light Detection and Ranging (LIDAR) system was also applied [18]. The system is still an expensive technology to date.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that UAV-LiDAR was used to obtain 3D point cloud information of ground objects, which generates a digital elevation model to obtain plant height of crops. This method has been applied to various crops, such as vegetable wheat ( Guo et al, 2019 ), corn ( Zheng et al, 2015 ), rice ( Tilly et al, 2014 ; Phan and Takahashi, 2021 ), soybean ( Luo et al, 2021 ), etc. The above results could better realize the analysis of crop phenotype indicators.…”
Section: Introductionmentioning
confidence: 99%